Massa de forragem, composição química do capim-massai e comportamento ingestivo de ovinos durante a fase de implantação do eucalipto em sistema silvipastoril - Andrade, Nomaiací de [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The implementation of silvopastoral system is increasing because of its potential to increase soil fertility, improve forage quality, promote thermal comfort, and provide diversification of income for the producer, achieving higher efficiency of animal production systems. The objective of this study was to determine the effects of silvopastoral system at different spacings of eucalyptus tree species in the development of eucalyptus, productivity of massaigrass and grazing behavior of sheep under intermittent grazing at conditions Jaboticabal - SP. The experiment consisted of three treatments with four replicates, varying the spacing between the rows of eucalyptus, these being: no shade (control treatment), presence of trees spaced 6 meters and 12 meters spacing. The variables: time (pre-and post-grazing), grazed stratum bulk density, rate of net accumulation, leaf / stem ratio, morphological components (dry mass of leaves, stem dry mass, dry mass of dead material), total dry forage chemical composition of the sample in simulated grazing, animal behavior and monitoring of eucalyptus. The analyzes of response variables massaigrass were performed according to a randomized block design with six replications in a repeated measures scheme. The height of eucalyptus has been reported in completely randomized blocks. Treatments were considered fixed effects and grazing cycles as random. The grass-massai physiologically responded to photoperiod decreased over the grazing cycles, resulting in significant effects (P <0.10) in morphological components, promoting the issuance of inflorescences. We observed higher mean crude protein on the first day collection on the third day compared with 8.04% and 5.29%, respectively, in the treatment of 6 meters. The treatments differed (P <0.10) for protein content, with the highest average observed in the treatment of 6 meters. The dry matter showed a linear effect (P <0.10) over the cycles, the third day ...

A crescente implantação de sistema silvipastoril é devido ao seu potencial em aumentar a fertilidade do solo, melhorar a qualidade da forragem, promover o conforto térmico animal, e proporcionar a diversificação de renda para o produtor, obtendo maior eficiência dos sistemas de produção animal. O objetivo do presente trabalho foi determinar os efeitos da fase de implantação do sistema silvipastoril com eucalipto em diferentes espaçamentos arbóreos sobre o desenvolvimento das árvores, produtividade do capim-massai e comportamento ingestivo dos ovinos manejados em pastejo intermitente nas condições edafoclimáticas de Jaboticabal – SP. O experimento consistiu em três tratamentos com quatro repetições, variando o espaçamento entre as fileiras de eucalipto, sendo estes: sem sombra (tratamento testemunha), presença de árvores com espaçamento de 6 metros e espaçamento de 12 metros. Foram analisadas as variáveis: altura (pré e pós-pastejo), estrato pastejado, densidade volumétrica, taxa de acúmulo líquida, relação folha/colmo, componentes morfológicos (massa seca de folhas, massa seca de colmo, massa seca de material morto), massa de forragem seca total, composição bromatológica da amostra colhida no pastejo simulado, comportamento animal e monitoramento dos eucaliptos. As análises das variáveis respostas do capim-massai foram realizadas segundo um delineamento em blocos casualizados, com seis repetições, em esquema de medidas repetidas no tempo. A altura do eucalipto foi avaliada em delineamento em blocos inteiramente casualizados. Os tratamentos foram considerados como efeitos fixos e os ciclos de pastejo como aleatórios. O capim-massai respondeu fisiologicamente a diminuição do fotoperíodo ao longo dos ciclos de pastejo, resultando em mudanças (P<0,10) nos componentes morfológicos, promovendo a emissão de inflorescências. Observou-se maiores médias dos teores de proteína bruta no primeiro dia ...
Keywords: Plantas forrageiras; Gramínea; Ovino; Ovino - Nutrição; Eucalipto; Sheep